The Gießen Tumor Documentation System (GTDS) – Review and Perspectives - Altmann, U.; Dudeck, J. (Methods of Information in Medicine, 2006)
Objectives: GTDS is a documentation system used by more than 40 German hospital cancer registries. This paper discusses the factors that contributed to its success concerning design, development, and routine use.Methods: Success is measured in terms of the system‘s financial independence of public grants and its successful use by the registries. Success factors are presented in a descriptive way covering the topics of development (tools and development team) as well as system‘s functionality and user support. The description of the system’s use and user satisfaction was collected in a user survey conducted in 1999.Results: GTDS has become the main tool in hospital cancer registries in Germany and remarkably contributed to their success. A comprehensive data network between hospital cancer registries and population-based cancer registries has especially been established in the new states. After the first years of routine use the registries produce valuable data analyses on the basis of common tools. Under specific conditions physicians use the system directly for treatment management. The system succeeded to be financed by support contracts for continuous development which indicates generally good user acceptance. Close interaction between users and developers is important to meet user requirements during development and maintenance.Conclusion: Important success factors are the strong ministry‘s support including initial sponsoring and introduction of support contracts, the comprehensive functionality as well as flexibility and broad user support which allow the adaptation to different environments.
Keywords: Cancer; tumor; registries; documentation; success factors; systems integration